Influence of drying methods over in vitro immuno-modulatory effect of polysaccharides from submerged fermentation by Agaricus Blazei - Fernandes, Marcelo Boscaro Alberca (2008)
Orientador: Prof. Dr. Carlos Ricardo Soccol